Public sentiments towards the use of Wolbachia-Aedes technology in Singapore - Christina Liew; Li Ting Soh; Irene Chen; Lee Ching Ng (BMC, 2021)
Abstract Background Wolbachia technology is a novel vector control approach that can reduce mosquito populations and the risk of mosquito-borne diseases, which has recently gained popularity amongst countries. In 2016, Singapore embarked on a multi-phased field study named Project Wolbachia - Singapore, to evaluate the use of Wolbachia technology as an Aedes aegypti mosquito population suppression tool to fight dengue. Due to the novelty of this technology in Singapore, this study aims to understand the public's acceptance and sentiments towards the use of Wolbachia technology. Methods Several public sentiment survey approaches - including online, face-to-face in the streets, as well as door-to-door household surveys - were conducted. Results The surveys conducted prior to the first field releases and implementation of the project revealed high support for the use of Wolbachia technology in Singapore. A household perception survey conducted in the interim of the first project phase was encouraging, with the majority of the respondents being aware of the project and having no concerns with the release of male Wolbachia-carrying Aedes aegypti (Wolbachia-Aedes) mosquitoes in their neighbourhood. Conclusions The study reveal high support for the use of Wolbachia technology in Singapore and also provided invaluable insights that were used in the development of a public communications and engagement framework model, which thus helped to guide these elements in the subsequent phases and expansion of the project.